2021
DOI: 10.1007/s10029-021-02519-0
|View full text |Cite
|
Sign up to set email alerts
|

A modified Delphi process to establish research priorities in hernia surgery

Abstract: Background Abdominal wall hernia repair is one of the most commonly performed surgical procedures worldwide, yet despite this, there remains a lack of high-quality evidence to support best management. The aim of the study was to use a modified Delphi process to determine future research priorities in this field. Methods Stakeholders were invited by email, using British Hernia Society membership details or Twitter, to submit individual research questions v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…11 Modified electronic Delphi process is commonly used to reach consensus and identify research priorities in diverse health areas. [12][13][14][15][16] Several frameworks have been used to guide the process of priority setting, including the James Lind Alliance Priority Setting Partnership (JLA PSP), 17 Essential National Health Research (ENHR) 18 and the Dialogue Model. 19 The JLA PSP method convenes patients, carers and clinicians to equally and jointly identify questions about healthcare that cannot be answered by existing evidence that are important to all groups (ie, research needs).…”
Section: Discussionmentioning
confidence: 99%
“…11 Modified electronic Delphi process is commonly used to reach consensus and identify research priorities in diverse health areas. [12][13][14][15][16] Several frameworks have been used to guide the process of priority setting, including the James Lind Alliance Priority Setting Partnership (JLA PSP), 17 Essential National Health Research (ENHR) 18 and the Dialogue Model. 19 The JLA PSP method convenes patients, carers and clinicians to equally and jointly identify questions about healthcare that cannot be answered by existing evidence that are important to all groups (ie, research needs).…”
Section: Discussionmentioning
confidence: 99%
“…Four articles reported outcomes; however, these were not standardized, and only one study 15 included patient-reported outcomes. The importance of patient-reported experience measures (PREMS) and patientreported outcome measures (PROMS) is increasingly acknowledged in hernia surgery, 19,20 though variation in questionnaires and tools used internationally makes result interpretation and comparison challenging. 21 Other limitations include low patient numbers in the studies reporting postoperative outcomes, which hindered direct comparison and meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…DOOR has more statistical power than analyzing outcomes separately or binary composites, like textbook outcomes. At every iteration, surgical DOORs used a modified Delphi process, a valid, established method to substantiate consensus among experts (and previously used to determine research priorities for various surgical specialties and a surgical safety checklist). Surgical DOORs demonstrated improved detection of complex SDOH relationships within private-sector cohorts .…”
Section: Introductionmentioning
confidence: 99%